Ammon's Horn, or, The Mystery of the Brain : A Novel - Magistretti, Pierre, 1952-; Magistretti, Christine (New York : Other Press, 2023)
"Spurred by his wife's Alzheimer's diagnosis and disenchanted with the slow progress of science in finding a cure, a rich Swiss businessman launches a contest for promising young neuroscientists who can think "outside the box." Five scientists compete for $100 million and the opportunity to head a new institute dedicated to research for the cure of Alzheimer's disease. Chosen on the basis of their scientific excellence and originality, they must travel throughout Europe in search of the answers to five fiendishly difficult riddles, each comprising an enigmatic neuroscientific question combined with a geographical and historical challenge. The personal stories of the competitors unfold while we follow and share with them their moments of elation and disappointment as they solve a riddle or reach a dead-end. Soon a conspiracy materializes to threaten and endanger the scientists in what seems at first a random way, but then becomes increasingly deliberate and targeted. The nature of the riddles and the talents of the competitors open a world of discovery for us, too, as we learn about some of the most pressing questions in current brain research, such as neurodegenerative diseases, stem cell grafts, artificial intelligence, drug addiction, genetics, and the mechanisms of memory. And as the candidates visit some of the great European cities-Prague, Vienna, Cordoba, Cambridge, Geneva, and Venice-we also step through a window into the past"--
Keywords: Thrillers (Fiction); Novels